Intensive woodland management in the Middle Ages: spatial modelling based on archival data - Szabó, Péter; Müllerová, Jana; Suchánková, Silvie; Kotačka, Martin (Journal of historical geography, 2015)
Firewood played an indispensable role in European socio-economic systems from prehistory until the nineteenth century. Recent research has shown that in European temperate lowlands the most important management form to produce firewood was coppicing. In spite of the growing body of research on traditional woodland management, there remain large gaps in knowledge. Detailed studies of individual sites or smaller areas have provided a wealth of information on the methods of medieval coppicing, and at such sites the long-term effects of coppicing on vegetation structure and composition have also been examined. However, little is known about the distribution and extent of coppicing at the landscape scale, and forming a coherent picture of the spatial extent rather than the management details of coppicing in larger regions remains a challenge. This paper investigates the distribution and extent of coppice management in Moravia (eastern Czech Republic, ca. 22,300 km2) in the Late Middle Ages. We created an extensive database of written sources that contained information on the presence of coppice woods at the parish level. Subsequently we used the MAXENT algorithm to create a model of the distribution of coppicing over the entire area. With the help of wood production and consumption estimates, we also calculated the minimum area of managed woodland for the study period. Results show that coppicing was predominant in the lowlands and often occurred at higher elevations as well, where neither natural conditions nor tree species composition were favourable. The paper also highlights the potential of spatial models based on archival data for historical landscape reconstructions.
Keywords: GIS; coppice; historical landscape reconstruction; Moravia; forest management; Middle Ages